Comparative technique diagnosis of the contact phase and push off performance in cross-country roller skiing - Veith, M.; Schwirtz, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Analysis of XC skating techniques deals with kinematic and kinetic aspects of upper and lower body motions and with resulting forces (Schwirtz, A., 1994). Studies concerning ground reaction forces showed different components of the total impulse (Lindinger S., 2006) but didn`t analyze them individually. In this study we are interested in how the total impulse gets generated and if there are different solutions regarding the economy of a contact and push off phase. METOHDS 4 trained XC skiers performed 3 trails on roller skis in the V1, V2, V2 alternate and V skating technique. Plantar pressure was measured over an interval of 30s with F-Scan® Mobile insole sensors and analyzed with the Fast Scan Mobil Research 6.31 software package. The sampling rate was 30Hz. The pressure data was normalized and converted to force by means of body weight. For each trail one average contact phase was calculated and the average of that 3 contact phases constitute one representative contact phase. For distinguished analysis both feet were divided into 4 areas: 1st total, 2nd front-interior (FI), 3rd front-exterior (FE), 4th back (BA). Point of view was impulse of each area per body weight and the shift of load from back to forefoot. RESULTS The range of the total impulse of V2 was within 9,6-6,8N/kg for the right and 9,6-7,2N/kg for the left foot. Individually there were no conspicuous differences in the intensity between the left and the right foot. The percentage composition of the total impulse of the left foot was: skier1 36% FI, 15% FE, 49% BA. Skier2: 30% FI, 17% FE, 53% BA. Skier3: 44% FI, 8% FE, 47% BA. Skier4: 42% FI, 19% FE and 39% BA. Data of the right foot showed no striking differences. Regarding the shift of load from back to front skier1 and 2 shifted at about 50% of the contact phase whereas the other skiers already shifted at about 25%. DISCUSSION Generating the total impulses the athletes showed variable distributions of the 3 sub impulses FI, FE and BA. Skier 3 and 4 generated almost the same resulting impulse as skier1 but already shifted load from back to forefoot at 25% of time while skier1 finally shifted at 48%. Skier3 shifted the load onto his forefoot at 42% of time but 52% of the resulting impulse was generated from the back of his foot. In comparison to skier1, skier 3 and 4 had longer stance on the forefoot, skier3 longer stance on the back foot. They had longer contraction times of the involved muscles and a less explosive rate in the final push off. This could imply less O2 supply and worse economy. Those aspects could play a role in a differentiated diagnosis of the contact phase in XC skiing. In this running study the other skating techniques will be analyzed as well. REFERENCES Lindinger S. (2006) Biomechanische Analyse von Skatingtechniken im Skilanglauf. Spektrum Bewegungswissenschaft, Band 4. Meyer&Meyer, Aachen. Schwirtz, A. (1994). Bewegungstechnik und muskuläre Koordination beim Skilanglauf. Sport und Buch Strauß. Edition Sport Köln. Köln.